Household Solid Waste Management Practices and Socioeconomic Condition in Muksudpur Municipality, Gopalganj, Bangladesh - Hossain, Md. Rajib; Rahman, Kazi Ashikur; Rahman, Md. Shamsur; Islam, Rifat; Biswas, Md. Shihab (Journal of Sustainability and Environmental Management, 2025)
Solid waste management is a significant environmental challenge in emerging Asian countries. This study was conducted in Dhaka Division’s Gopalganj district, focusing on household solid waste management in Muksudpur municipality. Urbanization, development, and population growth in Muksudpur municipality have led to increased household solid waste. It has been noted that residential garbage in every ward is not being handled properly, and no one seems concerned. The investigation found biodegradable, nonbiodegradable, recyclable, and reusable household waste. There is no trash can system or door-to-door pickup. The research region solely dumps trash into rivers or open spaces. This garbage harms humans and the environment. Organics, paper, plastics, and other minor components accounted for the majority of HSW in Muksudpur. Generally, population density and the health of the local economy are correlated with solid waste production. These items can be collected and disposed of securely at a lower cost, and the savings can be allocated to waste management. Before being removed from houses, this domestic rubbish must first be sorted by residents. The government should be worried about the storage, collection, transportation, and disposal of household waste in the Muksudpur municipal region, according to the project’s conclusions.